Light-driven Ti3C2 MXene micromotors: self-propelled autonomous machines for photodegradation of nitroaromatic explosives. Issue 26 (23rd June 2021) - Mayorga-Martinez, Carmen C.; Vyskočil, Jan; Novotný, Filip; Pumera, Martin
Abstract : Light powered self-propelled 2D-material MXene-based sandwitch micromachines degrade high-energy exposives on a go. Abstract : Self-propelled artificial micro/nano machines performing targeted tasks have recently attracted the research attention of materials scientists. Here, we prepare sandwich-like TiO2 @Ti3 C2 /Pt structures to serve as light-driven micromotors. A Pt layer is used to protect one side of the Ti3 C2 nanoflakes from oxidation and also enhances its photocatalytic activity. The other side of the Ti3 C2 nanoflakes is exposed and develops a TiO2 layer by oxidation. Such 2D material-based micromotors allow light-driven motion and on-the-move photodegradation of 2, 4, 6-trinitrotoluene. This work represents a new proof-of-concept for the use of two-dimensional materials for fuel-free light-driven micromotors with enhanced photodegradation ability toward environmental pollutants and explosives.